2018
DOI: 10.1128/iai.00944-17
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Mammalian Chitinase Negatively Affects Immune Responses during Acute and Chronic Aspergillus fumigatus Exposure

Abstract: Chitin is a polysaccharide that provides structure and rigidity to the cell walls of fungi and insects. Mammals possess multiple chitinases, which function to degrade chitin, thereby supporting a role for chitinases in immune defense. However, chitin degradation has been implicated in the pathogenesis of asthma. Here, we determined the impact of acidic mammalian chitinase (AMCase) () deficiency on host defense during acute exposure to the fungal pathogen as well as its contribution to-associated allergic asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 63 publications
(65 reference statements)
1
25
1
Order By: Relevance
“…The low-frequency/broadband forced oscillation technique was employed to measure Newtonian resistance (Rn; also known as airway hyperreactivity), tissue damping (G), and tissue elastance (H). All measurements were collected at baseline and after a linear dose response with methacholine challenge (10-40 mg/mL), as previously described (10,16). Lung function was also assessed in naive WT and mutant mice, which confirmed no baseline anomalies and no differences between groups, as we have previously reported (11).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The low-frequency/broadband forced oscillation technique was employed to measure Newtonian resistance (Rn; also known as airway hyperreactivity), tissue damping (G), and tissue elastance (H). All measurements were collected at baseline and after a linear dose response with methacholine challenge (10-40 mg/mL), as previously described (10,16). Lung function was also assessed in naive WT and mutant mice, which confirmed no baseline anomalies and no differences between groups, as we have previously reported (11).…”
mentioning
confidence: 82%
“…Regarding Il1rn -/mice, eosinophils were significantly decreased and neutrophils were significantly increased in whole lungs (Figure 6B), which is consistent with the lung lavage fluid data ( Figures 4B and Figure 5B). We have previously reported that IL-17A and IL-22 function in an immunopathogenic manner during experimental fungal-associated allergic airway inflammation (11,16). We recently reported that CD4 + T cells, as well as the innate lymphocytes γδ T cells, and invariant NKT cells (iNKT) cells were cellular sources of IL-22 (and likely IL-17A) in the lung during experimental fungal-associated allergic airway inflammation (10).…”
Section: Il-1ra Regulates the Severity Of Experimental Fungal-associamentioning
confidence: 99%
See 1 more Smart Citation
“…Chitotriosidase was also involved in lung diseases such as tuberculosis, chronic obstructive lung diseases [ 80 ]. Apart from chitotriosidase, acute exposure to the fungal pathogen Aspergillus fumigatus promoted the function of acidic mammalian chitinase, which determined the severity of fungal asthma [ 81 ]. Therefore, inhibition of chitotriosidase and acidic mammalian chitinase is regarded as a drug target for respiratory diseases [ 82 ].…”
Section: Potential Applications Of Chitin and Chitosan Oligosacchamentioning
confidence: 99%
“…ICSs have high efficiency in treating asthma but are only partially effective in controlling airway inflammation. Moreover, ICSs have been linked to adverse cardiovascular effects in COPD patients, growth stunts in pediatric CF bronchiectasis patients, and withdrawal complications [ 75 , 79 , 80 ]. The biggest limitation of these inhaled therapies is their inability to aid in regulating disease modification and/or progression.…”
Section: Mediators Of Chronic Inflammatory Airway Diseasesmentioning
confidence: 99%